Defining Variations in Outcomes of Hip Arthroscopy for Femoroacetabular Impingement Using the 12-Item International Hip Outcome Tool (iHOT-12). Issue 5 (April 2020) - Martin, RobRoy L.; Kivlan, Benjamin R.; Christoforetti, John J.; Wolff, Andrew B.; Nho, Shane J.; Salvo, John P.; Van Thiel, Geoff; Matsuda, Dean; Carreira, Dominic S.
Background: As health care moves toward a value-based payment system, it will be important that patient-reported outcome measures (PROMs) define variations in outcome over a follow-up period that allows a patient to achieve maximal improvement. Although there is evidence to support the use of PROMs to assess postoperative outcomes after hip arthroscopy, there is limited information available to assess for variations in outcome at a 2-year follow-up interval. Purpose: To identify substantial clinical benefit (SCB) and patient acceptable symptom state (PASS) cutoff scores for the 12-item International Hip Outcome Tool (iHOT-12) that define patient status across a spectrum of potential outcomes after hip arthroscopy at a 2-year follow-up interval. Study design: Cohort study (diagnosis); Level of evidence, 2. Methods: These data were collected from a research registry of patients having hip arthroscopy for femoroacetabular impingement and/or chondrolabral pathology. On initial assessment and 2 years (±2 months) postoperatively, patients completed the iHOT-12, and categorical self-rating of function. They also completed a visual analog scale of postoperative satisfaction. Receiver operator characteristic analysis was performed to determine absolute SCB iHOT-12 scores associated with an "abnormal, ""nearly normal, " or "normal" self-report of function, and PASS scores for those reporting at least 50%, at least 75%, or 100% satisfaction with their surgery. Results: Out of 723 eligible patients, 658 (91%) met the inclusion criteria. The patients consisted of 462 (70%) women and 196 (30%) men, with a mean age of 35.3 years (SD, 13 years) and mean follow-up of 722 days (SD, 69 days). Absolute SCB and PASS iHOT-12 scores ranging from 38 to 86 were accurate in identifying those who had abnormal, nearly normal, and normal self-reported function and were at least 50%, at least 75%, and 100% satisfied with surgery. The areas under the curve were >0.70, with sensitivity and specificity values ranging from 0.78 to 0.92. Conclusion: This study provides absolute SCB and PASS iHOT-12 cutoff scores that can be used to define variations in 2-year (±2 months) outcomes in patients after hip arthroscopy for femoroacetabular impingement and chondrolabral pathology. iHOT-12 scores of 38, 60, and 86 were associated with abnormal, nearly normal, and normal reports of function respectively, with scores of 60, 71, and 86 associated with at least 50%, at least 75%, and 100% satisfaction after surgery, respectively.